Strategic Changes in Russian Automotive Market (2018–2023) - D. V. Vorobeva; S. V. Shchelokova (Мир новой экономики, 2025)
Due to the crisis phenomena affecting the automotive industry since 2020 — such as the shortage in microelectronics during the COVID‑19 pandemic, the withdrawal of key manufacturers as a result sanctions against Russia in 2022, and the impact of unfavorable economic factor — passenger car sales in 2022 decreased by 979,410 units compared to 2021. This has led to the transformation of the Russian automotive market and the search by its participants for new revenue sources and business models. The aim of this study is to analyze the structure and dynamics of the transformation of the Russian automotive market from 2018 to 2023, focusing on the activities of key players (automakers, distributors, car dealers) and related sectors (carsharing, auto leasing, online sales aggregators, micro-mobility services), as well as to bridge the gap in academic research on this sector. Methods. To study the market structure and key trends in Russia and globally from 2018 to 2023, reports from major international consulting firms — AEB, Autostat, AutoBusinessReview — as well as Russian regulatory acts were analyzed. The systematization of business trends in the automotive sector was conducted using a PESTLE analysis, while an assessment of changes in the value chain was carried out through interviews with industry experts.